EFFICACY OF IPOMOEA PALMATA AS OVIPOSITIONAL DETERRENT, OVICIDE AND REPELLENT AGAINST BEETLE, CALLOSOBRUCHUS CHINENSIS (L.) - DWIVED, S.C.; KUMARI, AMITA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2000)
Ipomoea palmata was assayed for its various toxic properties against Callosobruchus chinensis (L.). Leaf extract of I. palmata was found to be effective as repellent, ovipositional deterrent and ovicide against C. Chinensis.